Anti-Müllerian Hormone in Peritoneal Fluid and Plasma From Women With and Without Endometriosis. (September 2015) - Hipp, Heather; Loucks, Tammy L.; Nezhat, Ceana; Sidell, Neil; Session, Donna R.
Anti-Müllerian hormone (AMH) has potential local effects on ovarian function and endometrial tissue, including endometriosis, but its presence in peritoneal fluid is not fully understood. This is a cross-sectional study evaluating AMH in peritoneal fluid and plasma from women with endometriosis (N = 61) and from control women without endometriosis (N = 36). There was a significant correlation between AMH in plasma and peritoneal fluid from both patients with endometriosis ( r 2 = .767 [ P < .001]) and control participants ( r 2 = .647 [ P < .001]) less than 45 years of age. Anti-Müllerian hormone declined with women's increasing age in both plasma and peritoneal fluid in women with and without endometriosis. There were no differences in the plasma or peritoneal fluid AMH in women with endometriosis versus control women. The strong relationship between plasma and peritoneal fluid may allow plasma AMH to be a marker for peritoneal AMH in studies evaluating the local effects of AMH.